Investigation the Citizen\'s Satisfaction from the elements of sense of belonging (Case study: Golha Residential Complex of Rasht) - Matin Farzidi; Reza Parvizi; Maryam Daneshshakib; SeyedReza Azadeh (تحقیقات کاربردی علوم جغرافیایی)
Nowadays, the lack of attachment is a significant point in the construction of towns, which is demonstrated with criteria such as lack of environmental attraction and visual qualities, lack of readability, security, and so on. These factors will affect people's relationship with the environment around them and thus their satisfaction. Golha Town faces numerous problems including lack of space for gatherings, lack of security and space confusion, inadequacy of appearance of the newly constructed buildings in relation to older monuments, and most importantly the existence of empty and unused land. The method used in this research is combinational including a set of descriptive-analytical methods. Data collection is performed using field and documentary methods. The statistical sample of the study was considered to be 384 people, based on the population of Rasht city. By distributing 420 questionnaires, 386 correct questionnaires were answered and returned. Analysis of questionnaires was performed by SPSS software. Measurement of selectivity, permeability and readability was also accomplished using the space syntax method and integration and connectivity analysis on the road adjacent to Golha town. The results showed that the impact of criteria such as readability, security and permeability was moderate. Visual proportions, elemental functions and access have a great effect on increasing the satisfaction of residents. As a result, the use of architectural patterns, considering pausing and moving spaces, creation of management applications, prevention of mass construction and indoor parks, are among the solutions to create the desired increase in satisfaction.